Analysis of Waste Management in the Pasar Lama Tangerang Area From a Sustainable Tourism Perspective - Lytiana Natalie; Ani Yanah; Barbie Valerina Tanu (Research Collaboration Community (Rescollacom), 2026)
The Pasar Lama Tangerang area is one of the culinary tourism centers and traditional trading hubs that holds significant historical and economic value in Tangerang City. However, the increasing commercial activities and the growing number of visitors have resulted in substantial waste generation that has not been managed optimally. This study aims to analyze waste management practices and perceptions in the Pasar Lama Tangerang area from the perspective of sustainable tourism, based on insights from field actors such as vendors and sanitation workers. This research employs a descriptive qualitative approach, with data collected through field observations, in-depth interviews, and documentation. The research subjects consist of vendors and sanitation workers in the Pasar Lama area selected using purposive sampling. Data were analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings indicate that waste management in the Pasar Lama Tangerang area remains conventional and does not fully align with the principles of 3R (Reduce, Reuse, Recycle). Limited sanitation facilities, low participation from vendors, and insufficient socialization from the area’s management serve as major obstacles to achieving a clean environment. These findings reflect the actual conditions and perceptions of field actors; therefore, they cannot yet be used as a basis for directly assessing government policies.